The Truth About Hierarchy - Sanner, Bret; Bunderson, J. (MIT Sloan Management Review, 2018)
Research on social species shows that hierarchies are important for group functioning. Human beings also have a tendency to think and act hierarchically. In fact, hierarchies - distinct differences in group members' power and status - can be found in virtually every human group, from children on the playground to executives in the boardroom. Although many people have argued that flat organizations promote innovative thinking, the authors maintain that a properly deployed hierarchy can help teams engage in and get the most out of their efforts to learn and innovate. Specifically, the authors observe that hierarchies help teams generate, identify, and select new ideas by performing three critical functions: bounding solutions, converging ideas, and structuring processes. "A paradox of creativity," the authors write, "is that people are more innovative when they have clear constraints (such as time, budget, customer requirements, etc.) within which their solutions must fit." Early on, teams tend to come up with an array of ideas and possibilities. Hierarchies, the authors explain, can help sort through which ideas should be pursued and which ones are less promising. The authors provide three recommendations for leaders seeking to leverage the power of hierarchy on teams and avoid its pitfalls. First, organizations should have a clear chain of command. In one study, teams with a clear chain of command were less likely to get bogged down in conflicts and stalemates than other teams. Second, organizations need to create performance-based cultures in which performance gets measured, publicized, and celebrated. Hierarchies in performance-based cultures are more likely to be based on expertise, and that can counteract unconscious biases against women and minorities. Third, people at the top of the organization should act in ways that support group goals as opposed to promoting their own interests. Citing a study one of the authors participated in, they write: "Hierarchies promoted learning and performance when goals and feedback were group-oriented, but they stifled learning and performance when goals and feedback were individually oriented."